Effect Of Electrical Muscle Stimulation On Disuse Muscle Atrophy In Subdural Hematoma - Kulkarni, Janhavi; B.Kanase, Suraj (Journal of Neonatal Surgery, 2025)
Background-Subdural hematoma (SDH) is a common intracranial haemorrhage associated with significant morbidity, often leading to prolonged immobilization and muscle atrophy. Disuse muscle atrophy, particularly in bedridden patients, results in loss of muscle mass and strength, impacting recovery and functional outcomes. Electrical muscle stimulation (EMS) has been explored as an intervention to mitigate muscle atrophy and enhance rehabilitation. Aim-This study aimed to evaluate the effectiveness of electrical muscle stimulation in preventing disuse atrophy in patients with subdural hematoma, compared to passive range-of-motion exercises alone. Methods-A total of 26 patients diagnosed with SDH and exhibiting muscle atrophy in the biceps brachii and quadriceps femoris were recruited. Participants were randomly assigned into two groups: Group A (EMS + Passive range of motion exercises) and Group B (Passive range of motion exercises only). The intervention was administered for six weeks, twice daily. Muscle girth measurements were recorded at baseline and post-intervention using circumferential measurements. Data were analysed using ANOVA and Kolmogorov-Smirnov tests. Results-Both groups showed significant improvement in muscle girth after six weeks (p < 0.0001). However, Group A demonstrated a significantly greater increase in muscle girth compared to Group B (p < 0.0001), indicating the superior effectiveness of EMS in preventing disuse atrophy. Conclusion-Electrical muscle stimulation, in addition to early exercise training, is effective in reducing disuse muscle atrophy in patients with subdural hematoma. The findings suggest that EMS can be a valuable adjunct to conventional rehabilitation strategies for immobilized patients.